The Routledge companion to feminist philosophy - Garry, Ann; Khader, Serene J.; Stone, Alison (Routledge philosophy companions, 2017)
"The Routledge Companion to Feminist Philosophy is an outstanding guide and reference source to the key topics, subjects, thinkers, and debates in feminist philosophy. Fifty-six chapters, written by an international team of contributors specifically for the Companion, are organized into five sections: (1) Engaging the Past; (2) Mind, Body, and World; (3) Knowledge, Language, and Science; (4) Intersections; (5) Ethics, Politics, and Aesthetics. The volume provides a mutually enriching representation of the several philosophical traditions that contribute to feminist philosophy. It also foregrounds issues of global concern and scope; shows how feminist theory meshes with rich theoretical approaches that start from transgender identities, race and ethnicity, sexuality, disabilities, and other axes of identity and oppression; and highlights the interdisciplinarity of feminist philosophy and the ways that it both critiques and contributes to the whole range of subfields within philosophy."--The publisher.
Keywords: afro-féminisme; approches et analyses; autonomie; bioéthique; care; cours; cycles supérieurs; discipline; environnement; esthétique; fem9000; féminisme africain; féminisme autochtone; féminisme décolonial; féminismes noirs; identité; injustices épistémiques; intersectionnalité; justice sociale; matérialité; objectivité; outils; ouvrages de références; philosophie; philosophie féministe; phénoménologie; politique de genre; queer; rationnalité; religion; sciences humaines; subjectivité; thématiques; théorie du contrat social; transféminisme; écologie; éthique; éthique du care; études critiques de la race; études critiques du handicap

What does queer theory teach us about intersectionality? - Duong, Kevin (Politics & Gender, 2012)
“What does queer theory teach us about x ?” ask Berlant and Warner (1995). “As difficult as it would be to spell out programmatic content for an answer, this simple question still has the power to wrench frames” (p. 348). This challenge comes from an early essay published to circumvent queer theory's appropriation. Its power “to wrench frames” is what I am posing to intersectional research, not only to reflect on what intersectionality has allowed feminists to accomplish but also to identify some existing shortcomings in the scope and domain of its employment. Because there is little disputing intersectionality's theoretical contribution to feminist research in the past decades—one scholar calls it “the most important theoretical contribution that women's studies . . . has made so far” (McCall 2005, 1771)—it is important for us to take stock of the sorts of political problems that intersectional scholarship has addressed and the ones to which it has often been inattentive.
Keywords: approches et analyses; cours; cycles supérieurs; fem9000; intersectionnalité; queer; ressource en ligne

“I would rather be a cyborg than a goddess” Becoming-intersectional in assemblage theory - Puar, Jasbir K. (philoSOPHIA, 2012)
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem9000; intersectionnalité; philosophie; queer; ressource en ligne; sciences humaines